Invited discussant - Pavoni, A. (Aerocommoning in the Digital Age: Exploring a ‘Right to Breathe’ at the Intersection of Digital Humanitarianism, Decentralised Rights, Spatial Justice, and Science Journalism’ 22-24 June, 2023)
: ‘Aerocommoning in the Digital Age: Exploring a ‘Right to Breathe’ at the Intersection of Digital Humanitarianism, Decentralised Rights, Spatial Justice, and Science Journalism’, organised by the University of Westminster and the Logische Phantasie Lab at the Abbey Sutton Courtenay, Oxford,